Implementation of a Web-Based Boarding House and Rental Search and Booking Information System Using the Waterfall Method - Sembiring, Falentino; Hidayat, Rahmat; Irawan, Peri (Primakara University, 2026)
The rapid development of information technology has increased the need for a more efficient and structured housing search system for students. This study aims to develop an integrated web-based information system for searching and booking boarding houses and rental properties in accordance with user requirements. The development method employed is the Waterfall model, which consists of the stages of Requirement Analysis, System Design, Implementation, and Testing. Data were collected through observations of Facebook social media, questionnaires distributed to 81 students, and interviews with 10 boarding house owners. The system was developed using PHP with the Laravel framework and a MySQL database. System testing was conducted using Black-box Testing and User Acceptance Testing (UAT) involving 20 respondents, resulting in a user satisfaction rate of 87.4%. The findings indicate that the developed system enhances the efficiency of housing searches and facilitates the online booking process. With a structured approach grounded in empirical needs, the system is considered effective and feasible as a web-based solution for searching and booking boarding houses.